Survey Pemanfaatan Pangan Lokal Untuk Mencegah Anemia Pada Ibu Hamil Di Puskesmas Alak Wilayah Kerja Kota Kupang - Floriana Layu Gening (STIKes CHMK, 2018)
Anemia is the decrease of red blood cells (erythrocyte) in blood circulation or in hemoglobin mass resulting in blood’s inability to fulfill its function as oxygen carrier to tissues in the body. During pregnancy, women need adequate nutrition such as carbohydrate, protein, fat, vitamins e.g. Vitamin C, folic acid, and iron. Local foods are foods that are native to and originally harvested from a certain area and can be directly used for consumption. In this context, foods that are regarded local are corn, cassavas, nuts, vegetables, and fruits. This research aims to identify how those foods are utilized in the effort of preventing anemia in pregnant women in the working area of Alak Public Health Centre of Kupang City. This research is descriptive in nature with survey design. 95 respondents were chosen through consecutive sampling technique. Instruments used in this research were questionnaires. Based on the data, it was concluded that most pregnant woman make use of local foods to prevent anemia. Among the local foods that are mostly used are corn, beans (green beans, red beans, and other beans), cassavas, and varieties of yams. Keywords: Local Foods And Anemia